Pentingnya pemenuhan gizi pada indeks massa tubuh dan aktivitas fisik - Sari, Indah Prasetyawati Tri Purnama; Kriswanto, Erwin Setyo; Dwihandaka, Riky; Broto, Danang Pujo; Alim, Abdul Mahfudin (Universitas Nusantara PGRI Kediri, 2020)
Malnutrition troubles body mass index and physical activity. This study aims to analyze the relation of fulfillment of Nutrition on body mass index and physical activity. This research is a correlational study supported by survey methods. Data collection technique employs questionnaires and measurements of body weight and height. The population in this study is elementary school students in Sleman Yogyakarta and a sampling technique employs purposive random sampling. The total samples are 236 students. The research instrument uses 24-hour food recalls to determine fulfillment of Nutrition; tanita weight scales, microtoise to measure body mass index, and GPAQ (Global Physical Activity Questionnaire) to determine physical activity. Furthermore, analysis technique employs Pearson correlation analysis. The data analysis results of fulfillment of Nutrition and body mass index obtain syndication calculations 0.00 <0.05, meaning there is a relationship between the fulfillment of nutrition and body mass index. Additionally, the data analysis results of fulfillment of Nutrition and physical activity obtain significance calculation 0.00 <0.05, which means there is a relation between fulfillment of Nutrition and physical activity. Briefly, there is significant relation between the fulfillment of nutrition and body mass index as well as between the fulfillment of nutrition and physical activity. In another words, the study shows positive link between fulfillment of Nutrition with body mass index and physical activity.